Prevalence of Preeclampsia in Pregnant Women at Dayaku Raja Hospital, Kutai Kartanegara Regency, East Kalimantan, 2018 - Indarto, Fanny; Deviana, Deviana; Hasan, Jafri; Winarko, Tjatur Budi; Kaban, Yunita Eliana Intan (Jurnal MedScientiae, 2022)
Currently Low Back Pain (LBP) is a major global health problem with an annual prevalenceof 22% - 65%. Many things are the cause of LBP such as spinal deformities from birth,trauma, age, pregnancy and body mass index (BMI). Several previous research are stillcontroversial whether the relationship of body mass index with incidence of low back pain.The design of this study was cross sectional descriptive analytical with the aim to see therelationship between body mass index and the incidence of low back pain in medicalstudents. This research was carried out at Ukrida Medical Faculty with a sample of 216people with 64.4% respondents were female and men 35.6%, and respondent whoexperienced mild low back pain were 94.9%, moderate at 5.1%. Based on body mass index,the majority of respondents had a normal BMI of 55.6%, underweight of 6.9%, then overweight of 37.5% and those who experienced mild pain based on visual analogue scale of79.6%, no pain at 10.2%, moderate pain 8.8%, then controlled severe pain is 1.4%. Afterstatistical tests using Pearson Chi-Square obtained results there is a relationship betweenbody mass index and the incidence of low back pain with p = 0.043.